Retificação de Inconel 718 com multicamadas de grafeno dispersas em fluido de corte aplicado via técnica MQL - Oliveira, Déborah de (2017)
Due to the small size of the chips and the low thermal conductivity of the conventional grinding wheels, most of the heat generated in the grinding process goes to the workpiece. Depending on the amount of heat, it can adversely affect surface finish and cause microstructural changes in the workpiece material that may compromise its functionality. This problem becomes worse when machining superalloys, such as Inconel 718, which also has low thermal conductivity and consequently leads to low rate of heat dissipation during machining. For this reason, the grinding of this alloy with conventional grinding wheels is generally carried out at high coolant flow rates in order to cool the workpiece. However, in the last years, various research has been focused on restriction of the use of high volume of coolants because of health and environmental risks related to their use. Therefore, it is necessary to seek alternatives for cutting fluids that combine good refrigeration with lower risks to human health and the environment. Among the several possibilities, this research investigated the influence of multilayer graphene platelets added to a vegetable-based cutting fluid on the surface roughness, surface and subsurface changes of the Inconel 718 after grinding with SiC grinding wheel, as well as on the grinding power. Two different concentrations (%wt) (0.05% and 0.10%) of multilayer graphene were tested and applied via the MQL technique. Tests with graphene-free coolant also applied via MQL technique, flood and dry condition were also performed to allow comparisons. The results showed that grinding with the lowest graphene concentration applied via the MQL technique (MQL MG 0.05%) provided the lowest roughness values and microhardness variation, as well as required less grinding efforts. It was also able to reduce the generation of cracks in the surfaces and resulted in compressive residual stress after grinding under less severe conditions. The microhardness was influenced by the coolinglubrication technique and the radial depth of cut. The MQL MG 0.05% condition proved to be technically viable as an alternative to the use of flood technique in the grinding of Inconel 718 with conventional abrasive wheel.